Local and systemic delivery of a stable aspirin-triggered lipoxin prevents neutrophil recruitment in vivo - Clish, Clary B. (The National Academy of Sciences, 1999)
Aspirin (ASA) triggers a switch in the biosynthesis of lipid mediators, inhibiting prostanoid production and initiating 15-epi-lipoxin generation through the acetylation of cyclooxygenase II. These aspirin-triggered lipoxins (ATL) may mediate some of ASA’s beneficial actions and therefore are of interest in the search for novel antiinflammatories that could manifest fewer unwanted side effects. Here, we report that design modifications to native ATL structure prolong its biostability in vivo. In mouse whole blood, ATL analogs protected at carbon 15 [15(R/S)-methyl-lipoxin A(4) (ATLa(1))] and the omega end [15-epi-16-(para-fluoro)-phenoxy-LXA(4) (ATLa(2))] were recoverable to ≈90 and 100% at 3 hr, respectively, compared with a ≈40% loss of native lipoxin A(4). ATLa(2) retains bioactivity and, at levels as low as ≈24 nmol/mouse, potently inhibited tumor necrosis factor-α-induced leukocyte recruitment into the dorsal air pouch. Inhibition was evident by either local intra-air pouch delivery (≈77% inhibition) or systemic delivery by intravenous injection (≈85% inhibition) and proved more potent than local delivery of ASA. Rank order for inhibiting polymorphonuclear leukocyte infiltration was: ATLa(2) (10 μg, i.v.) ≈ATLa(2) (10 μg, local) ≈dexamethasone (10 μg, local) >ASA (1.0 mg, local). Applied topically to mouse ear skin, ATLa(2) also inhibited polymorphonuclear leukocyte infiltration induced by leukotriene B(4) (≈78% inhibition) or phorbol ester (≈49% inhibition), which initiates endogenous chemokine production. These results indicate that this fluorinated analog of natural aspirin-triggered lipoxin A(4) is bioavailable by either local or systemic delivery routes and is a more potent and precise inhibitor of neutrophil accumulation than is ASA.